Pengaruh Pertanian terhadap Pendapatan Nasional - Maryam Batubara; Marlinda Mustika Pane (Jurnal Penelitian Ekonomi Akuntansi, 2023)
The agricultural sector is one sector that is the focus of attention in economic growth. Where economic growth is marked success based on the amount of national income. The method used in this study is to use library research which originates from books, journals, articles. (both in print and electronic form). The conclusions of this study are: first, the agricultural sector has a significant influence on the country. Second, the agricultural sector is one of the sectors supporting national economic growth, especially when there is an economic crisis. Third, although the agricultural sector is said to be good, it is known that there is still a lack of productivity, human resources, capital and even technological innovation that is still lagging behind neighboring countries. Fourth, the success of the national income is one of them influenced by the succeeding of the agricultural sector, while the successful of the Agricultural sector cannot be separated from government policies themselves.